Ta’thīr al-ḥarakah al-salafīyah bi Miṣr ‘alà al-mujaddidīn bi Indūnīsiyā fī taṭwīr al-tarbīyah al-Islāmīyah - Zarkasyi, Amal Fathullah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
This article discusses the influence of Salafiyah movement in Egypt on the Indonesian Muslim reformers in developing Islamic education. Salafiyah movement in Egypt led by Jamaluddin al-Afghani, Muhammad Abduh and Muhammad Rasyid Rida has affected many Muslim activists in Indonesia. The entry of this movement to Indonesia was through the Indonesian students who returned from their study in Egypt. This Influence can be traced to the development and modernization of Islamic education in Sumatra such as the establishment of Madrasah Tawalib, Islamic University of Sungayang, Madrasah of Normal Islam, Madrasah Diniyah. From Sumatra, it spreads to Java, Sulawesi and Kalimantan, marked by the establishment of schools by Muhammadiyah organization, Persis, Al Irsyad and Darussalam Islamic boarding school Gontor, Madrasah As’adiyah in Sulawesi, Jami’ah Islamiyah Sultaniyah and Normal Islam in Kalimantan. From those Islamic educational institutions, Islamic universities were born in Indonesia.DOI: 10.15408/sdi.v20i2.389